Exploring the Dynamics of Price Competitiveness and Tourism Openness in Enhancing Bandung City’s Local Revenue - Asterina Anggraini; Annisa Wardhani; Meisa Sofia; Nuraeni Hadiati Farhani; Diara Nazifa Rizqi Kamalia (Bisnis Event, 2026)
This study analyses the dynamics of the Price Competitiveness Indicator (PCI) and Openness Indicator (OI) in driving Bandung City's Local Own-Source Revenue (PAD) during the 2019-2023 period. A quantitative descriptive method with trend analysis was used to map the changing patterns of these three variables. The results show that PCI has a strong positive correlation with PAD, where a sharp decline in 2020 due to the COVID-19 pandemic was followed by a significant recovery through 2023. In contrast, the contribution of OI to PAD was relatively small and weak, although it showed an increasing trend post-pandemic. The study's conclusion indicates that price competitiveness is the main short-term driver of PAD, while openness is more strategic for long-term growth. The policy implication is the need for a balance between price stabilization strategies and enhancing destination openness.